The Role of Tax Volunteers for the Nation in Enhancing Tax Compliance and Tax Literacy at KPP Pratama Jakarta Kembangan - Riswari Asri Rabbani; Irwan Harefa; Yananto Mihadi Putra (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
Taxes are the main source of state revenue and play an important role in supporting national development. Therefore, improving taxpayer compliance is a major concern for the government. This study aims to evaluate the role of the Tax Volunteer Program for the Nation (Renjani) in assisting with annual tax return reporting and providing tax education to the public. The approach used is descriptive qualitative, involving direct observation of the implementation of the Tax Volunteer Program at the Kembangan Tax Office in Jakarta from February to May 2025. Volunteers consisting of accounting students from Mercu Buana University provided technical assistance to taxpayers and created educational content through social media. The results of the activities showed that volunteers successfully helped overcome various challenges in filing tax returns, such as data entry errors, system connection issues with the Tax Office, and verification challenges. On the other hand, the digital content created successfully reached the public and improved online tax literacy. The conclusion of this study is that volunteer involvement not only supports tax compliance but also helps in the application of tax accounting principles and tax planning through practical and communicative education.